Arbitration in Syrian Law: Forms and Applications - محمد عمار; فواز صالح (Latakia University Journal - Economic and Legal Sciences Series, 2025)
In light of the development and complexity of commercial relationships, the need for arbitration as an effective dispute resolution method has become pressing. Arbitration offers speed and confidentiality in resolving disputes, as well as flexibility that surpasses traditional judicial systems. This trend reflects countries’ commitment to regulating arbitration as a legal alternative for resolving conflicts, including Syria, which has developed a comprehensive legal framework for arbitration. According to Syrian Arbitration Law No. 4 of 2008, arbitration is recognized as an alternative method for resolving disputes instead of litigation. Commercial arbitration is considered the optimal way to resolve disputes due to its many advantages, such as expertise, flexibility, procedural speed, and confidentiality. These advantages make arbitration a desirable alternative for effectively resolving commercial disputes. Arbitration in Syrian law is viewed as a flexible and effective means for resolving disputes, whether through an arbitration clause before the dispute arises or an arbitration agreement after it has occurred. Both institutional and ad hoc arbitration allow parties to choose the model that best suits their specific needs.